Bioimaging predictors of rilpivirine biodistribution and antiretroviral activities. (December 2018) - Ottemann, Brendan M.; Helmink, Austin J.; Zhang, Wenting; Mukadam, Insiya; Woldstad, Christopher; Hilaire, James R.; Liu, Yutong; McMillan, JoEllyn M.; Edagwa, Benson J.; Mosley, R. Lee; Garrison, Jered C.; Kevadiya, Bhavesh D.; et al.
Abstract: Antiretroviral therapy (ART) has changed the outcome of human immunodeficiency virus type one (HIV-1) infection from certain death to a life free of disease co-morbidities. However, infected people must remain on life-long daily ART. ART reduces but fails to eliminate the viral reservoir. In order to improve upon current treatment regimens, our laboratory created long acting slow effective release (LASER) ART nanoformulated prodrugs from native medicines. LASER ART enables antiretroviral drugs (ARVs) to better reach target sites of HIV-1 infection while, at the same time, improve ART's half-life and potency. However, novel ARV design has been slowed by prolonged pharmacokinetic testing requirements. To such ends, tri-modal theranostic nanoparticles were created with single-photon emission computed tomography (SPECT/CT), magnetic resonance imaging (MRI) and fluorescence capabilities to predict LASER ART biodistribution. The created theranostic ARV probes were then employed to monitor drug tissue distribution and potency. Intrinsically 111 Indium ( 111 In) radiolabeled, europium doped cobalt-ferrite particles and rilpivirine were encased in a polycaprolactone core surrounded by a lipid shell ( 111 InEuCF-RPV). Particle cell and tissue distribution, and antiretroviral activities were sustained in macrophage tissue depots. 111 InEuCF-PCL/RPV particles injected into mice demonstrated co-registration of MRI and SPECT/CT tissue signals with RPV and cobalt. Cell and animal particle biodistribution paralleled ARV activities. We posit that particle selection can predict RPV distribution and potency facilitated by multifunctional theranostic nanoparticles. Graphical abstract: Highlights: Theranostic antiretroviral nanoparticles form intracellular macrophage drug depots. Coordinate SPECT/CT or MRI signal intensities and UPLC MS/MS measured ARV concentrations. ICP-MS for theranostic particle metal detection can validate ARV tissue concentrations. Bioimaging can provide a rational platform to predict ARV nanoparticle tissue biodistribution. Complex physicochemical biodistribution characteristics not predicted by available mathematical modeling can be affirmed through theranostic platforms.